Carbon-based electrodes with large geometric dimensions

By installing carbon-based electrodes in the conductive material frame, the problem of difficulty in producing large geometric carbon-based electrodes in the prior art is solved, and the production of large geometric surface area electrodes and uniform current density distribution are realized, which is suitable for large volume reactants deal with.

CN111758177BActive Publication Date: 2025-02-14VLAAMSE INSTELLING VOOR TECHNOLOGISCH ONDERZOEK NV (VITO)
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN201880064601.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2018-06-05
Filing Date
2018-09-21
Publication Date
2025-02-14
Estimated Expiration
2038-09-21

AI Technical Summary

Technical Problem

The prior art is difficult to produce carbon-based electrodes with large geometric sizes, and the mechanical strength of the large-sized electrodes and ohmic losses during operation are large, which cannot effectively solve the space and component requirements required for large-volume reactant treatment.

Method used

By using a frame made of conductive materials, carbon-based sub-electrodes are mounted using cutouts, and conductive connections of sub-electrodes are ensured through conductive integration, a carbon-based sub-electrode has a large geometric surface area.

Benefits of technology

The production of carbon-based electrodes with large geometric surface areas is achieved, ensuring homogeneous electrode properties and uniform current density distribution, reducing the mechanical strength and ohmic loss requirements of the electrodes, and is suitable for the treatment of large volume reactants.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN111758177B_ABST
    Figure CN111758177B_ABST
Patent Text Reader

Abstract

The present invention relates to a carbon-based electrode with a large geometric surface area, which includes a frame of a conductive material having several cutouts with surface areas, the cutouts being separated from each other by portions of the conductive material, wherein a carbon-based sub-electrode sized to cover at least the surface area of ​​the cutout is positioned in the cutout and conductively connected to at least a portion of each of the portions of the conductive material adjacent to the carbon-based sub-electrode.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] The present invention relates to a carbon-based electrode with an increased surface area compared with existing carbon-based electrodes, and in particular to a carbon-based electrode with a larger geometric surface area compared with existing carbon-based electrodes.

[0002] Electrochemical reactions have attracted significant interest because the technology opens up new possibilities for more efficient use of resources and allows direct conversion of electrical energy into chemical energy (or vice versa) while reducing the generation of waste heat. Among other things, reaction rates and selectivity can be controlled by adapting one or more of the electrode potential, catalyst, surface structure and concentration of one or more reactants in the electrochemical cell. In electrochemical cells in which gaseous reactants undergo oxidation or reduction reactions, porous gas diffusion electrodes contained therein have been identified as key but decisive components.

[0003] The industrial applicability of electrochemical conversion technologies has been found to be largely dependent on the scale of development. The availability of electrochemical reactors in large sizes and cost-effective designs is an essential requirement if economically viable electrochemical conversion technologies are envisaged.

[0004] An electrochemical reactor may be composed of a plurality of single electrochemical cells electrically connected in either a monopolar or bipolar arrangement. In a bipolar arrangement, bipolar plates connect electrically adjacent cells in series, and the electrons generated or consumed in the electrochemical reaction flow in a direction perpendicular to the plane of the electrodes along the bipolar plates. The bipolar plates also connect the anode of one cell and the cathode of an adjacent cell. In a monopolar arrangement, all cathodes are electrically connected in parallel, and all anodes are electrically connected in parallel, and the entire assembly is immersed in a single electrolyte bath or tank.

[0005] Current monopolar carbon-based electrodes typically consist of a layer of electrochemically active material, especially a catalytically active material layer arranged in a porous activated carbon material matrix, which is typically applied on top of a porous conductive current density distributor. The current density distributor typically takes the form of a porous grid. The current density distributor adds the required in-plane conductivity to the electrode in the direction along the direction of the main current flow, and can also add in-plane conductivity in the cross direction of the main current flow. The current density distributor further provides mechanical and dimensional support to the electrochemically active layer of the electrode. Metal grids or meshes with low electrical resistance made of various alloys with a wide range of thickness and opening area combinations are commercially available and are typically used as current density distributors. A specific example of such a current density distributor developed by VITO is described in PCT application PCT / EP2014 / 053737.

[0006] Given the geometric dimensions of 0.5 to 1m 2Electrochemical reactors with electrodes on the order of 1000 Å are available in large quantities, for example when the active surface of the electrode is metal. The application of carbon-based gas diffusion electrodes is practically limited to the use of single cells with a maximum size of several hundred cm. 2 The processing of large volumes of reactants accordingly requires an arrangement in which a large number of individual electrochemical cells, each equipped with a gas diffusion electrode, are connected in a direction perpendicular to the electrode plane, which results in an impractical demand in terms of space and components.

[0007] Unfortunately, the production of large-sized carbon-based electrodes is not self-evident. Porous carbon electrode materials are inherently brittle and fragile, and therefore the production of large thin electrode sheets or plates requires special manufacturing techniques (such as casting or calendaring) and a high degree of craftsmanship. In addition to these challenges already encountered in the manufacture of gas diffusion electrodes, simply increasing the size of the electrode presents further disadvantages, such as mechanical strength of the electrode and ohmic losses during operation.

[0008] Efforts to solve manufacturing limitations are mainly tailored around adaptations in the composition of the active layer, such as described, for example, in Japanese patent publications JPH04169070, US 4777083 and JPS63130791, but these solutions are generally incompatible and they depend on the properties of the active layer. Welding several plate-shaped electrodes on top of a geometrically large conductive substrate as described in EP1229149A1 cannot be considered a technology suitable for use with carbon-based electrodes, and certainly not suitable for use with carbon-based gas diffusion electrodes, because neither of these two components - the electrodes or the support plate - allow gas diffusion. In addition, the space between adjacent electrodes has insulating properties, and the presence of the welding material creates a voltage potential different from the voltage potential already present in the electrodes.

[0009] In JPH04169070, two carbonaceous powders of different particle sizes are mixed and used as filler components of the adhesive, with the purpose of forming an adhesive layer in which conductive fine particles are contained inside the thermosetting resin when baked and carbonized. The viscosity of the adhesive should be maintained between 500-5000 poise, and the adhesive should be formed in a layer 50-200 μm thick. The adhesive layer is bonded to the porous carbonaceous electrode plate to harden under pressure and heating, and is baked and carbonized at 800°C or above in a non-oxidizing gas. However, this method for producing electrodes is harsh, energy-consuming and therefore expensive.

[0010] From the above, it is apparent that carbon-based electrodes having larger geometries than hitherto known or used cannot be obtained simply by linearly scaling up the size of existing carbon-based electrodes.

[0011] Analogous to geometrically large sheet metal electrodes, it has therefore become desirable to provide carbon-based electrodes having geometric dimensions that are significantly larger in length and width than hitherto known. In an ideal situation, the large electrode should be suitable for use with both anodes and cathodes in gas diffusion electrodes.

[0012] The present invention therefore seeks to solve the problem of providing a carbon-based electrode of geometrically large dimensions suitable for use with both anodes and cathodes in gas diffusion electrodes.

[0013] According to the invention, this problem is solved by means of a carbon-based electrode showing the technical features of the characterizing part of the first claim.

[0014] Therefore, the present invention relates to a carbon-based electrode having a large geometric surface area. The electrode comprises a frame of a conductive material having a plurality of cutouts with surface areas, the cutouts being separated from each other by portions of the conductive material, wherein a carbon-based sub-electrode sized to cover at least the surface area of ​​the cutout is positioned in the cutout and conductively connected to at least a portion of each of the portions of the conductive material adjacent to the carbon-based sub-electrode.

[0015] In such a carbon-based electrode, due to the conductive integration, the entire active electrode surface area will be formed by the combined surface area of ​​each individual sub-electrode. In addition, the conductive integration of the sub-electrodes into the frame ensures good mechanical robustness. The advantage presented by the present invention is that the manufacturing process currently used to manufacture the sub-electrodes can be maintained and does not need to be adapted to make the sub-electrodes suitable for use with the present invention. Since the sub-electrodes are not positioned on top of a continuous supporting metal plate, but are assembled in a cutout or gap in a supporting conductive frame or the like, the accessibility of the two opposite sides of the active surface of the sub-electrode is ensured and the diffusion of the reaction gas from the two opposite sides of the sub-electrode to the catalytically active layer is allowed. Thus, the individual catalytic activity of each of the sub-electrodes can at least be maintained.

[0016] In addition, depending on the arrangement of the sub-electrodes in the frame, homogeneous electrode properties can be ensured over the entire surface area of ​​the large geometric surface area of ​​the electrode and a uniform current density distribution can be ensured. However, if desired, by means of a different arrangement of the sub-electrodes, the electrode properties can also be anisotropic or they can vary over the electrode surface according to a desired pattern.

[0017] The present invention presents advantages over the prior art in terms of the need for a larger electrode area for carbon-based electrodes, in which several electrodes are stacked in a direction perpendicular to the electrode plane, to allow a reduction in the volume or space required for a reactor capable of treating a large volume of liquid per unit time. When it is necessary to treat a large volume per unit time, the stacking approach results in a large space required for installation and in a large number of expensive cell components and peripheral equipment. The present invention allows such costs associated with the large number of cell components required for peripheral equipment to be kept to a minimum.

[0018] The present invention provides a solution to the problem that carbon-based electrodes with large geometric dimensions cannot be produced simply by linearly scaling up the size of existing carbon-based electrodes. From a technical point of view, this can be difficult to achieve, since homogeneous electrode properties need to be ensured over the entire surface of the electrode, and sufficient mechanical and dimensional stability must be ensured regardless of the possible up to 0.5 to 1 m. 2 The invention also solves the problem of ensuring a suitable and uniform distribution of the current density over the entire surface area of ​​the electrode - or, if desired, a varying current density distribution.

[0019] In order to minimize the risk of potential difference at the interface where a carbon-based sub-electrode is conductively connected to at least a portion of each of the portions of conductive material adjacent to the carbon-based sub-electrode, a preferred embodiment of the present invention is characterized by the following: each of the sub-electrodes includes a current density distributor, and the current density distributor of each of the sub-electrodes is connected to at least a portion of each of the portions of conductive material adjacent to the carbon-based sub-electrode including the current density distributor.

[0020] In order to minimize the risk of potential differences occurring at the interface where the carbon-based sub-electrodes are conductively connected to the frame of the conductive material, the frame and the current density distributor of the sub-electrodes have different but preferably identical conductivities to the smallest possible extent. When it is mentioned that the frame and the current density distributor of the sub-electrodes have different conductivities to the smallest possible extent, it is meant that the conductivity of the frame can differ from the conductivity of the current density distributor by a maximum of 10%, preferably by a difference of 5%. This can be achieved in particular by the frame and the current density distributor being made of the same conductive material.

[0021] The carbon-based electrode of the present invention is further characterized by the following: the frame is made of a conductive material having a resistance equal to or less than the resistance of the current density distributor of the sub-electrodes. This ensures a uniform current density distribution over the entire surface area of ​​the carbon-based electrode with a large geometric surface area.

[0022] The invention also relates to an electrochemical cell comprising at least one carbon-based electrode having a large geometric surface area as described above. Typically, the at least one carbon-based electrode will serve as a cathode.

[0023] Except this at least one negative electrode, electrochemical cell according to the present invention will further comprise at least one anode usually.In order to increase power density and further improve the performance of electrochemical cell, and in the case of the water purification device in order to increase COD, anode or the array comprising several anodes can be connected to two or more carbon-based electrodes as described above to provide anode.In a preferred embodiment, the opposite side of each anode is connected to more carbon-based electrodes as described above.

[0024] Since the surface area of ​​the cathode is generally the limiting factor, in an electrochemical cell according to the invention the cathode will preferably have an active surface at least 5 times larger, preferably at least 10 times larger, more preferably at least 20 times larger or even more than the active surface of the anode.

[0025] In order to improve the performance of the cathode, even for an electrochemical cell having a larger volume, a sub-electrode of a carbon-based electrode having a large geometric surface area located in a lower position in the electrochemical cell closer to the bottom of the electrochemical cell preferably has a smaller porosity than a sub-electrode of a carbon-based electrode having a large geometric surface area located in a higher position in the electrochemical cell closer to the upper part of the electrochemical cell. According to another embodiment, a different cathode may be used at the bottom of a water chamber where the water pressure is greatest compared to a cathode at the top of a water chamber where the water pressure effect is much smaller.

[0026] The carbon-based electrodes of the present invention are suitable for use in many applications, such as in electrochemical synthesis using carbon-based electrodes, in electrochemical waste stream disposal using carbon-based electrodes. The carbon-based electrodes of the present invention are suitable for use as air cathodes in microbial fuel cells (MFCs), such as for disposal of sewage (in pilot-scale MFC devices of size ~ 1000 liters). In this application, the cathode will be permeable to air on one side and impermeable to water on the other side, and exhibit catalytic activity, as further described below. In a preferred embodiment, the electrochemical cell further comprises at least one anode, wherein the opposite side of each anode is connected to the carbon-based electrode, as this allows for increased power generation and increased COD removal rates.

[0027] The invention is further explained in the drawings and description of the drawings.

[0028] Figure 1 A metal frame is shown having 15 cutouts for mounting 15 sub-electrodes therein.

[0029] Figure 2 A schematic representation of a frame having cutouts for mounting sub-electrodes therein is shown.

[0030] Figure 3 A cross section in the thickness direction of the electrode of the present invention is shown.

[0031] Figure 4 shows that Figure 4A )50mM PBS (6.25mS cm –1 )and( Figure 4B ) with NaCl (1.45 ± 0.05 mS cm –1 ) in tap water corrected with respect to the cathode in the small chamber (SC), the middle chamber (MC) and the large chamber (LC), measured in the electrochemical cell of Example 1 as a function of current density.

[0032] Figure 4C and D shows that in ( Figure 4C )50 mM PBS (6.25 mS cm–1) and ( Figure 4D )Corrected (corr) and uncorrected (not corr) cathode potential as a function of current density measured in an electrochemical cell for cathodes in the small chamber (SC) and the middle chamber (MC) in tap water with NaCl (1.45 ± 0.05 mS cm–1) and an electrode spacing (d_(WE-RE)) of 1.15 cm.

[0033] FIG. 5 shows the cathode (Ct) potential from the biopolarization test and the non-bioelectrochemical test of Example 2 and the Figure 5A ) Omuro and ( Figure 5B ) chamber for the biopolarization test, Figure 5C ) Biopower density curves in small chamber (SC) and large chamber (LC) MFC, ( Figure 5D ) Measured anode potentials in LC and SC (not corrected for ohmic drop) and estimated anode potential in SC with increased electrode spacing of 3.45 cm. Figure 5E Shown are chronopotentiograms of the cathode in a large (85 L) chamber in 50 mM PBS and in tap water amended with NaCl (LCS) in the presence (Sp) and absence (NS) of a separator. Fig. 5F Shown are chronopotentiograms of the cathode in the large (85 L) chamber in 50 mM PBS in the absence of a separator (NS) and by blowing additional air through the air chamber at a flow rate of 0.5 liters per minute (air 0.5 Lpm).

[0034] FIG. 6 shows a schematic diagram of a Fig. 6A ) compared with the non-biological chronopotentiometry data in 8 (projected area = 0.25 m 2 ) and 22 anode brushes (projected area = 0.60m2 ) of the anode module, and the cathode potential (Ct) and anode potential (An), and ( Figure 6B ) corresponding to the power density curve.

[0035] The present invention relates to a carbon-based electrode with a large geometric surface area. According to the present invention, when referring to a carbon-based electrode with a large geometric surface area, it means that its geometric surface area is at least 4 times larger than that of the carbon-based electrodes of the prior art, preferably at least 5 times larger, more preferably at least 10 times larger, most preferably at least 50 times larger, especially at least 100 times larger or even at least 500 times larger than that of the existing carbon-based electrodes.

[0036] In the context of the present invention, a carbon-based electrode having a large geometric surface area may also refer to an electrode having a length of at least 20 cm, preferably at least 30 or 40 cm, more preferably at least 50 cm, or at least 75 or even at least 100 cm, and a width of at least 20 cm, preferably at least 30 or 40 cm, more preferably at least 50 cm, or at least 75 or even at least 100 cm. A person skilled in the art will appreciate that the length and width of the carbon-based electrode may be the same or different.

[0037] In the context of the present invention, a carbon-based electrode having a large geometric surface area may also refer to an electrode having a total surface area (i.e. including the surface area occupied by the framework, framework parts and sub-electrodes) of at least 400 cm 2 , preferably at least 900 or 1600 cm 2 , more preferably at least 1000 cm 2 , or at least 75 or even at least 100 cm, and a width of at least 20 cm, preferably at least 30 or 40 cm, more preferably at least 50 cm, or at least 5500 cm 2 Or even at least 10 4 cm 2 .

[0038] The shape of the carbon-based electrode is not critical to the present invention and can be selected by the skilled person taking into account any requirements imposed by its intended use. The carbon-based electrode may have a regular or irregular shape, symmetrical or asymmetrical. The carbon-based electrode may, for example, have a substantially circular shape, which may be oval, rectangular, square or any other suitable shape.

[0039] from Figure 1As can be seen, the carbon-based electrode 1 of the present invention comprises a frame 10 made of a conductive material, in which several cutouts 20, 21, 22, 23 are provided. Such a frame can be obtained in various ways well known to those skilled in the art, for example by appropriately shaping the conductive material into a frame, by removing parts from a conductive sheet of a plate, or by connecting parts of the conductive material in such a way that a frame 10 with several cutouts is formed, or in any other suitable way.

[0040] Adjacent cutouts are separated from each other by portions 11, 12 of conductive material. The portions 11, 12 may be made of the same or different conductive materials, but preferably, they are made of the same conductive material. The perimeter edge of the carbon-based electrode may include a perimeter frame 5, which may be made of the same material as the portions 11, 12 of conductive material (which is preferred), or the frame 5 may be made of a different material. Similarly, the portions 11, 12 may be made of the same or different materials. In order to keep the ohmic drop as small as possible, in other words, to reduce the portion of the resistance of the electrode applied by the frame and to keep the power output as high as possible, the distance between adjacent sub-electrodes is preferably kept as small as possible. This actually means that the size of the portions of conductive material present between the cutouts is kept as small as possible. The size of the portions of conductive material between the frame and the cutouts is preferably selected so that the geometric surface area they occupy is less than 30% of the total geometric surface area of ​​the electrode, more preferably less than 25%, most preferably less than 20%, especially less than 15% or even less than 10%. This will also allow the portion of the active electrode surface area to be increased relative to the total surface area of ​​the electrode.

[0041] The number of cutouts is not critical to the invention and can be selected and varied by a person skilled in the art taking into account the surface area of ​​each individual cutout and the electrochemical performance to be achieved by the electrode. The electrochemical performance is understood to also refer to the potential shown by the electrode at a certain current density or the voltage or voltage output or power density produced.

[0042] The shape of the cutout is also not critical to the present invention, and it can be selected and varied by those skilled in the art considering the shape of the frame 10 of the conductive material. The cutouts 20, 21, 22, 23 can be arranged in a random manner in the frame 10, but preferably, they are arranged according to a regular geometric pattern to ensure that the current is distributed as uniformly as possible on the electrode. The size of the cutout is also not critical to the present invention, as long as they do not adversely affect the mechanical and dimensional stability of the sub-electrodes installed therein. The size of the cutout will preferably correspond to the size of conventional carbon-based electrodes frequently used in the art, especially gas diffusion carbon-based electrodes. Suitable sizes are but not limited to a width of about 5 to 50 cm and a length of about 5 to 50 cm, and 20X20 cm is a frequently used size. Preferably, a sub-electrode is installed in each cutout.

[0043] The carbon-based electrode of the electrode of the present invention can be used as either an anode or a cathode, but is preferably used as a cathode.

[0044] The carbon-based sub-electrodes suitable for mounting in a frame of conductive material as described above typically include one or more current density distributors 8, with a layer of electrochemically active or catalytically active material on a carbon support 3 embedded in a porous polymer matrix and arranged on one side 18 or surface of the current density distributor. If desired, a water-repellent layer 13 or a hydrophobic gas diffusion outer layer can be added on top of the catalytically active layer, which allows the reaction gas to diffuse into the catalytic reaction layer while preventing the electrolyte from leaking out of the electrolyte chamber through the electrode. These electrodes are customized for use in those electrochemical cells in which the anode and cathode are separated by a free electrolyte liquid phase (e.g., an aqueous reaction medium, a sewage stream).

[0045] A "water repellent layer" (WRL) or hydrophobic gas diffusion layer 2 is understood to include a layer of hydrophobic material having an outer surface in contact with the gas and showing porosity to the gas, and having the ability to prevent leakage of aqueous electrolyte into the gas diffusion layer. An "electrochemically active layer" (EAL) is a layer in which electrochemical reactions occur, having high electrical conductivity and porosity to gas and electrolyte, and having an interface with the electrolyte on one surface and a water repellent (hydrophobic gas diffusion) layer on the other surface.

[0046] The entire surface of the current density distributor 8 may be covered by the EAL and WRL respectively or only a portion thereof. In order to ensure the best connection of the sub-electrode to the conductive material frame, it may be desirable to make the peripheral band 15 of the sub-electrode free of catalytically active materials and hydrophobic materials, and thereby provide a connection area for each sub-electrode. The size of the band 15 in the width direction of the band is preferably such that a liquid-tight connection to each portion of the conductive material adjacent to the sub-electrode and the frame can be ensured, so as to minimize the risk of cross contamination (e.g., reactants leaking from one side of the electrode to the other side). This is particularly important when the sub-electrode is a gas diffusion electrode, which generally includes a hydrophilic catalytically active layer on one side of the current density distributor and a porous hydrophobic gas diffusion layer that is permeable to gas but impermeable to liquid on the opposite side of the current density distributor. When used in an electrochemical reactor, the electrode of the present invention acts to separate different electrolytes from each other on either side of the active layer of the sub-electrode.

[0047] The liquid-tight connection between the sub-electrode (preferably the perimeter band) and the relevant part of the conductive material of the conductive frame can be achieved according to various methods known to those skilled in the art. Particularly suitable methods include welding or soldering, because those techniques allow the establishment of a mechanically strong connection with good pressure resistance and minimal risk of creating potential differences across the connection between the sub-electrode and the parts of the conductive frame. Other liquid-tight connections can be achieved by the presence of a sealing material along the perimeter edge of the sub-electrode, which holds the sub-electrode in the cutout in a liquid-tight manner (e.g., a rubber gasket).

[0048] Suitable examples of current density distributors for use in sub-electrodes of the present invention are disclosed in US2016 / 0010227. Preferred current density distributors can be in the form of porous meshes (e.g., woven, knitted or braided materials), with porosity provided by holes between woven-knitted or braided fibers. The current density distributor can also take the form of a web, a mesh, a plate, a sheet, a foil, a film or a sieve, and holes are provided therein, for example, using photochemical etching or electroforming. The current density distributor can be made of a variety of conductive materials, such as metals, metal-plastic combinations, mixed metal types, mixtures of metals and other non-metallic conductions (such as conductive polymers and conductive carbon, such as graphite, graphene and carbon nanotubes), and any combination thereof. Specific examples of conductive materials suitable for use with the present invention include intrinsic conductive polymers (ICPs), metal alloys. Preferred conductive materials include stainless steel alloys, more preferably austenitic stainless steel and duplex stainless steel (due to its high yield strength and stress corrosion cracking resistance to chlorides compared to austenitic stainless steel). Austenitic stainless steel and duplex stainless steel are preferred because of their good corrosion resistance and minimal magnetic properties. The size of a particular current density distributor is preferably adapted to the size of the cutout in which it is to be installed. The size of the current density distributor can be selected so that it fits into a particular cutout. Alternatively, the size of the current density distributor can be selected so that some overlap of the edge of the current density distributor and the edge of the cutout into which it is installed is provided to facilitate installation and a liquid-tight connection.

[0049] As already described above and as Figure 2 As shown, the carbon-based electrode 1 of the present invention comprises a frame 10 made of a conductive material, in which several cutouts 20, 21, 22, 23 are provided. Preferably, in each cutout, the carbon-based sub-electrode as described above is installed in a liquid-tight manner. Thus, all sub-electrodes can be the same. However, within the scope of the present invention, the sub-electrodes in different parts of the frame can also be different. This may be of particular interest if an electrochemical cell having a large volume is used, in which there is a considerable pressure difference between the upper part of the battery or chamber and the lower part near the bottom of the battery or chamber. In the case of a large volume battery, it may be preferred to provide a smaller porosity in the lower part of the frame sub-electrode and a higher porosity in the upper part of the frame sub-electrode.

[0050] The invention is further illustrated in the following examples.

[0051] Materials and methods

[0052] Electrode Materials

[0053] Several cathodes of different sizes (18×18 cm, 324 cm 2 , 0.45 mm thick). A PTFE diffusion layer (porosity 70%) was then added on top of the catalytically active layer containing the catalyst, which became the air side of the cathode.

[0054] Small room (11.3cm 2 ) and middle room (52cm 2 ) are made from the parts cut from these sheets. A circular cathode with a diameter of 3.8 cm (11.2 cm 2 ) was used for the smallest reactor (0.028 L), and 9.2 x 5.6 cm (52 ​​cm 2 ) was used in the medium reactor (0.22 L). The large cathode (107 cm long by 64 cm high, 0.68 m 2 ) contains 15 sub-cathodes that have been welded to a single stainless steel panel with 15 holes cut into it to provide a frame. One side of the cathode is exposed to water, while the other side is exposed to air. Using a single metal panel allows a low resistance of <0.2Ω to be obtained between the center of each sub-cathode and any other part of the outer stainless steel panel.

[0055] For chamber MFC tests of different sizes, two different sizes of brush anodes were made. For smaller reactors, the brush had a diameter of 2.5 cm and a length of 2.5 cm, and was made of a graphite fiber (PANEX 35 50K, Zoltek) wound between two titanium wires (Mill-Rose, Mentor, OH). The brush used in the larger reactor had a diameter of 5.1 cm and a length of 61 cm, made of the same material as the smaller brush (Gordon Brush (brush), CA, USA). All anodes were heat treated for 30 minutes in the air at 450 ° C before being used in MFC.

[0056] Bench and pilot-scale reactors

[0057] Three different electrochemical cells were constructed to evaluate the effect of scaled-up cathode size on electrochemical performance (Table 1). The smaller cell (SC) was a single-chamber cubic reactor that has been used in many previous MFC laboratory studies and was constructed from a 4-cm long polycarbonate block (5 cm × 5 cm) with an inner cylindrical chamber of 3 cm in diameter (total volume 0.028 L) and an exposed cathode area of ​​7 cm.2 (Table 1). The cathode specific surface area is 25m 2 m –3 Anode electrolyte volume.

[0058] Table 1 Basic specifications of three different sized test chambers

[0059]

[0060] The medium cell (MC) is a polycarbonate rectangular reactor with an anode chamber 10.9 cm long, 3.5 cm wide and 6.2 cm high, filled with 0.22 liters of electrolyte. The cell has a bracket slot 3.5 cm from the water side wall, where the cathode is attached, separating the anolyte chamber from the air cathode chamber. The cathode is fixed to the frame with screws using plastic U-shaped fasteners and washers (butyl rubber). The air chamber is 6.8 cm long, 1.0 cm wide and 4.4 cm high.

[0061] The large cell (LC) is a specially designed tank (1.1 m long, 0.15 m wide and 0.85 m high) that is used to examine the physical properties of the cathode, such as mechanical strength (deformation when filled) and water pressure resistance (based on leakage), as well as to evaluate the electrochemical properties of the cathode. The tank has a bracket slot 10 cm from the water side wall, where the cathode is attached to form the anolyte chamber. The cathode is fixed to the frame with screws using plastic U-shaped fasteners and washers (closed-cell PVC vinyl foam). The anolyte tank is filled with 85 liters of water and is visually inspected for deformation and leakage when filled. The cathode specific surface area is 7.3m 2 m –3 The cathode air chamber is formed by sliding a PVC sheet into a slotted groove 5 cm from the cathode. To reduce deformation of the cathode due to water pressure, the space between the transparent PVC sheet and the cathode is filled with 19 spacers. 32 , which was constructed by rolling a polypropylene net (XN3110-48P, Industrial Netting, USA) into a 1-m-long 4-cm diameter tube and holding the rolled tube together using cable ties.

[0062] In order to check the actual power generation in the large chamber, anode modules made of polyvinyl chloride (PVC) were constructed using a linear array of graphite fiber brushes. The PVC module holds 8 or 22 brushes (as noted), wherein the ends of the brushes are fixed at the top and bottom of the module. In initial tests, the brush module is placed parallel to the cathode in the middle of the anode chamber, thereby producing a distance of 3.45cm between the edge of the anode brush and the cathode. The anode is connected in parallel with the circuit by an external single titanium wire. At the top of the anode module, a fixture is used to reduce the bending of the cathode sheet and fix it in place and improve electrical connection. For smaller chambers, the anode is horizontally placed in the middle of the MFC chamber (perpendicular to the cathode), wherein the distance between the brush edge and the cathode is 1.4cm.

[0063] To avoid any short circuit and reduce the growth of biofilm on the cathode, all reactors were operated with a separator placed on the cathode (PZ-1212, Contec, USA). 34,35 For the small chamber, separators with the same cathode area were cut from 30 cm by 30 cm wipe separators (PZ-1212, Contec, USA). In the large chamber, 12 separators were sewn together and cut to the same final area as the cathode (0.68 m 2 ).

[0064] Electrochemical tests were performed using a potentiostat (VMP3, BioLogic, Knoxville, TN) with the cathode as the working electrode (WE) and a steel mesh as the counter electrode (CE) in the middle and large chamber reactors, and a Pt mesh as the CE in the small chamber. The electrochemical performance of the cathode was evaluated using chronopotentiometry (CP) tests in 50 mM phosphate buffer solution (PBS; Na2HPO4, 4.58 g L-1; NaH2PO4·H2O, 2.45 g L-1; NH4Cl, 0.31 g L-1; KCl, 0.13 g L-1; pH 7.0; conductivity κ = 6.25 mS cm-1) or sodium chloride-amended tap water (κ = 1.45 ± 0.05 mS cm-1) in the presence or absence of a separator. The current was fixed in the range of 0 to -4 mA in the small reactor, 0 to -10 mA in the medium chamber, and 0 to -0.4 A in the large chamber for 20 minutes. An Ag / AgCl reference electrode (RE-5B, BASi, West Lafayette, IN; +0.209 V vs. SHE) was used in the SC and MC electrochemical tests and was placed 1.15 cm from the cathode. The ohmic losses due to the distance between the RE and WE were corrected based on the conductivity of the solution (see SI and Figure 4C and 4DFor all experiments, an immersed reference electrode (AGG, Electrochemical Devices Inc., OH; +0.199 V vs. SHE) was used in the large chamber and was kept close to the cathode in the same position. All potentials are reported relative to the SHE.

[0065] Microbial fuel cell (bio) testing

[0066] The anode in the SC reactor was fully preconditioned to the sewage in the MFCs at a fixed external resistance of 1000Ω at a constant temperature (30°C) for more than four months. Domestic sewage was collected once a week from the effluent of the primary clarifier of the Pennsylvania State University Wastewater Treatment Plant and stored at 4°C before use. Single cycle polarization tests were performed by changing external resistances of 1000, 500, 200, 100 and 75 at 20-minute intervals after an open circuit in a constant temperature chamber (30°C) for 2h (and a total test duration of 3.7h).

[0067] The LC MFC was operated at room temperature and fed directly with fresh primary effluent. During the anode adaptation period of the first week of operation, the feed solution was 35 L primary effluent and 40 L containing 0.5 g L –1 A mixture of 50 mM PBS containing sodium acetate and 10 L of effluent collected from MFC feed acetate and sewage over several weeks. The external resistance was 1000 Ω for the first two days and then decreased to 100 Ω, 25 Ω, 10 Ω and 5 Ω every day. For the second week of adaptation, the solution was 55 L sewage, 20 L containing 0.5 g L –1 50 mM PBS with sodium acetate, and 10 L MFC effluent. Thereafter, only primary effluent was used to operate the LC MFC. After the voltage generated a stable cycle of up to three consecutive fed-batch cycles, a single cycle polarization test was performed using the LC MFC by feeding the reactor with fresh sewage and keeping the system under open circuit conditions for up to 2 h, and then varying the external resistance from 100, 25, 10, 5, 2, 1 to 0.4 Ω at 20 min intervals.

[0068] The current was calculated based on the voltage drop (U) across an external resistor and recorded using a computer-based data acquisition system (2700, Keithley Instrument, OH). The current density (i) and power density (P) were normalized to the total exposed projected cathode area (large chamber area, ALC = 0.62 m 2 , and power PLC; chamber area, ASC = 7cm 2, and power PSC), and is calculated as i=U / RA and P=iU, where R is the external resistance. During each polarization test, the anode and cathode potentials were also recorded using a reference electrode. An Ag / AgCl reference electrode (RE-5B, BASi, West Lafayette, IN; +0.209 V vs. SHE) was used to measure the anode potential (EAn) in a small chamber (SC) bioassay at a distance of 1.15 cm from the cathode. The cathode potential (ECt) was calculated from the anode potential and the cell voltage as ECt=U+EAn, and then corrected based on the conductivity of the solution and the distance from the RE (see SI and Figure 4C and D). An immersed reference electrode (AGG, Electrochemical Devices Inc., OH; +0.199 V vs. SHE) was used in the large chamber (LC) bioassay to measure the cathode potential (ECt), and it was kept close to the cathode and in the same position for all experiments. The anode potential (EAn) was estimated using the cell voltage as EAn = U-ECt and then corrected based on the conductivity of the solution and the distance from the RE (see SI and Figure 4C and information in D).

[0069] Chronopotentiometry tests on cathodes of different sizes showed differences in performance, with smaller cathodes producing the lowest overpotentials at different set current densities ( Figure 4A , Figure 4C and D). For example, at 0.61 ± 0.00 A m –2 The small cathode produced 0.35 ± 0.00 V at 0.62 ± 0.01 A m–2, which is only 5% higher than the voltage produced by the medium cathode (0.33 ± 0.00 V at 0.62 ± 0.01 A m–2), but higher than that obtained with the large cathode (0.64 ± 0.00 A m–2). –2 The detrimental effect of increased size of the electrode on performance is consistent with previous studies showing a loss in power with increasing cathode size.

[0070] Example

[0071] Example 1

[0072] The cathodes of different sizes were tested by chronopotentiometry in tap water amended with sodium chloride (κ = 1.45 ± 0.05 mS cm–1) to evaluate the performance of an unbuffered solution with a conductivity similar to domestic sewage ( Figure 4B ). The overpotentials of all cathodes are larger in the less conductive solution, with the large cathode having a much higher overpotential at a given current density relative to the other two cathodes.–2 0.23±0.00V at the cathode and 0.62±0.00A m –2 Compared with 0.26±0.01V at 0.64A m –2 The current density is 0.09±0.01V.

[0073] Additional chronoamperometry tests were performed using the large chamber to evaluate the effect of the presence of the separator on the electrochemical performance of the cathode over a range of current densities relevant to operation of larger MFCs using wastewater ( Figure 4C ). The presence of the additional wipe layer reduced the voltage output at 0.64A m–2 from 0.16 ± 0.03 V to 0.13 ± 0.01 V in PBS and from 0.09 ± 0.01 V to 0.06 ± 0.00 V in low conductivity solutions. Insufficient airflow in the cathode chamber reduced oxygen availability and cathode performance. Therefore, additional electrochemical tests were performed by blowing air into the bottom of the chamber at 0.5 Lpm ( Figure 4D ). This gas flow across the cathode did not affect cathode performance, indicating that the size of the gas chamber was sufficient to passively provide oxygen transfer to the cathode.

[0074] Example 2 Power production of 85L MFC fed with domestic sewage (22 anodes).

[0075] After adapting the 85 L MFC with the anode module within three fed-batch cycles, 13 polarization tests were performed using domestic sewage. The maximum power density was 0.083 ± 0.006 W m –2 , which is higher than the power density obtained in the small chamber MFC (0.304±0.009 W m –2 ) was 73% lower. The cathode potentials were similar in abiotic and biotic tests in the 85L and 28mL reactors ( Figure 5A and 5B ). For the small chamber, there was a significant difference between the OCVs for the biological test (0.32 ± 0.00 V) and the abiotic test (0.44 ± 0.00 V), but the cathode potentials were well matched over the current density range relevant for operation of the sewage-fed MFC. Anode performance was a factor in the reduced power production of the large MFC compared to the small MFC. Correcting the anode potential in the small chamber for the larger electrode spacing (3.45 cm in the LC and 1.4 cm in the SC) resulted in higher anode performance than recorded from the biological test in the LC (see Figure 5E For example, the slope of the trend line from the linearization of the anodic potential in the LC biotest is 0.56 Ωm–2, which is smaller than the 0.34 Ωm–2 from the SC biotest corrected for the larger electrode spacing. –2 65% higher ( Figure 5DHowever, the cathode performance (|0.30 V|, from 0.37 ± 0.04 V at OCV to 0.46 ± 0.03 A m –2 There is a change in the anode performance (|0.13 V|, from -0.31 ± 0.01 V at OCV to 0.46 ± 0.03 A m –2 This large difference in the cathode indicates that in this system, the cathode is the primary limiter of power generation. The reduction in anode performance is likely the result of both increased anode size and cathode performance. The anodes in the 85L MFC are much longer and have a larger diameter than those in the small MFC, both of which may result in higher overpotentials. The increase in water pressure may also have reduced cathode performance, especially at the bottom of the MFC where the water pressure is highest relative to the top of the reactor. This change in cathode performance may have affected the performance of the anode relative to the cathode in the bottom of the large reactor. The reduced effective area of ​​the cathode due to the metal frame may also be a factor in reducing anode performance, as the metal frame accounts for 23% of the exposed projected area of ​​the cathode. Normalizing for the power produced by the active cathode area alone would yield 0.10 W m –2 power density.

[0076] Example 3 Power generation of 85L MFC fed domestic sewage using 8 anodes.

[0077] To further examine the effect of the anodes on performance, tests were performed using 8 anodes instead of 22. Reducing the number of anodes reduced the anode projected area by 58% (from 0.60 m2 to 0.25 m2), but this only reduced the maximum power density by 27%, based on the cathode projected area from 0.083 ± 0.006 W m –2 To 0.061±0.003W m –2 (Figure 6). The power normalized to the projected anode area was 0.152 ± 0.009 W m –2 , which is consistent with previous results showing that larger cathode areas improve the relative performance of cathodes. Reducing the number of anodes results in a slightly increased anodic overpotential. For example, compared to 0.250 ± 0.006 A m with 22 anodes, –2 The anode potential was 0.206 ± 0.006 A m with 8 anodes, compared with –0.16 ± 0.01 V at the highest current density. –2 The maximum power density (normalized to the cross-sectional or projected cathode area) is at -0.121 ± 0.002 V. Thus, maximizing the full coverage of the cathode by the anode will allow for increased power generation. 37 .

[0078] Example 4 Power generation using 22 anodes.

[0079] MFCs with 8 or 22 anodes achieved similar COD removal efficiencies of 75-80%. Thus, the presence of a higher number of anodes does not increase the COD removal rate, although the number of anodes does affect the amount of COD converted into electricity. When 22 anodes were used, the coulombic efficiency 38CE was 27%, but when 8 anodes were used, it decreased to 13%.

[0080] Example 5 Effect of electrode spacing.

[0081] In Examples 1-4, a 3.45 cm electrode spacing was used. The solution resistance in the large chamber with an electrode spacing of 3.45 cm was 0.47 Ω, which is 21% of the internal resistance of the reactor (2.19 Ω). Reducing the spacing from 3.45 cm to 1.4 cm can reduce the internal resistance by 60% to 0.19 Ω and increase the maximum power density.

[0082] Example 6

[0083] The cathode was manufactured to include a 316L stainless steel mesh current density distributor and an activated carbon catalyst, with specifications described below:

[0084] Using 50 mM phosphate buffer and acetate as fuel, the current density is >0.3 A / m2.

[0085] Using 50mM phosphate buffer and acetate as fuel, the maximum power density is >100

[0086] mW / m2.

[0087] Water pressure resistance: Will not show visible leakage at water head pressure >3ft (>1m).

[0088] The variability of cathode performance (current density, power density and maximum water pressure resistance) across the full range of manufacturing is ≤ 10%.

[0089] The cathode piece meets the size requirements of the demonstration reactor (1.07 m wide x 0.64 m long).

[0090] Step 1: 15 VITOs Fabrication of gas diffusion electrode (20*20 cm2).

[0091] Each single electrode has the following characteristics:

[0092] Flat sheet, rectangular, PSA max. 20x20 cm, total thickness approx. 0,07 cm

[0093] Has a hydrophobic gas diffusion outer layer (the white layer in the image below);

[0094] Active layer (mesh layer: based on activated carbon; activated carbon: PTFE black layer ratio 80:20

[0095] Current density distributor: Stainless steel 316L supplied by Solana, wire diameter 0,02cm, mesh opening 0,045cm; 200x200mm

[0096] Step 2: Use 1070x 640mm from TESTAS, Belgium 2 A conductive metal frame for the assembly of the electrodes is realized from a stainless steel 316L plate. Spaces for mounting the carbon-based electrodes are laser cut from a metal plate made of a material that also acts as a conductive current density distributor for each individual electrode above the stainless steel 316L. The metal frame and the metal mesh of the current density distributor of the electrode consist of the same metal; the thickness of the metal frame is 2.5 times the thickness of the wire forming the metal mesh. The electrical conductivity of these materials is the same, but due to the greater thickness of the frame, the frame has a lower resistance than the conductive current density distributor present in the sub-electrode.

[0097] Step 3: Assemble the Gas Diffusion Electrode onto the Metal Frame

[0098] This is done by laser welding the wire mesh or edges of the metal mesh of the GDE to the metal frame. The total thickness of the assembly is no greater than the thickness of a single electrode.

[0099] In order to achieve a liquid-tight composition of the thin-plate electrode, the welded connection between the conductive frame and the (sub) electrode is sealed. This can be done by applying a sealing material around the weld edges to ensure the tightness of the assembly. A two-component glue (MacroPlast from Loctite) is applied to the seams / joints on the white layer side (gas feed side), which is allowed to dry for up to 2 days.

Claims

1. A carbon-based electrode having a total geometric surface area greater than 400 cm², the electrode comprising a frame of a conductive material having a plurality of cutouts with a surface area, the cutouts being separated from each other by portions of the conductive material, wherein a carbon-based sub-electrode sized so as to cover at least the surface area of ​​the cutouts is positioned in the cutouts and conductively connected to at least a portion of each of the portions of the conductive material adjacent to the carbon-based sub-electrode, wherein each of the sub-electrodes comprises a current density distributor, wherein the conductivity of the frame differs from the conductivity of the current density distributor by a maximum of 10%, and / or wherein the frame has a resistance equal to or less than the resistance of the current density distributor.

2. The carbon-based electrode according to claim 1, characterized in that wherein the current density distributor is connected to at least a portion of each portion of the conductive material adjacent to the carbon-based sub-electrode including the current density distributor.

3. The carbon-based electrode according to claim 2, characterized in that The frame has the same electrical conductivity as that of the current density distributor.

4. The carbon-based electrode according to claim 3, characterized in that The frame and the current density distributor of the sub-electrode are made of the same conductive material.

5. The carbon-based electrode according to any one of claims 1 to 4, characterized in that The carbon-based sub-electrode fits into the cutout in a watertight manner.

6. The carbon-based electrode according to claim 5, characterized in that A sealing material is applied to the connection of the sub-electrodes to the frame.

7. The carbon-based electrode according to claim 1, characterized in that The frame of conductive material is made of metal.

8. The carbon-based electrode according to claim 1, characterized in that The carbon-based electrode is a gas diffusion electrode.

9. The carbon-based electrode according to claim 1, characterized in that The dimensions of the frame and of the portions of conductive material between the cutouts are selected such that the geometric surface area of ​​the portions of conductive material between the cutouts accounts for at most 30% of the total geometric surface area of ​​the electrode.

10. The carbon-based electrode according to claim 1, characterized in that The sub-electrode located in the first portion of the electrode has a porosity smaller than a porosity of the sub-electrode located in the second portion of the electrode.

11. The carbon-based electrode according to claim 1, characterized in that The electrodes have a total surface area of ​​at least 900 cm2.

12. An electrochemical cell comprising at least one carbon-based electrode according to any one of claims 1 to 11 as cathode.

13. The electrochemical cell according to claim 12, characterized in that Further comprising at least one anode.

14. The electrochemical cell according to claim 13, characterized in that The cathode has an active surface that is at least 5 times larger than the active surface of the anode.

15. The electrochemical cell according to any one of claims 12 to 14, characterized in that A sub-electrode of the carbon-based electrode with a large geometric surface area located in a lower position in the electrochemical cell closer to the bottom of the electrochemical cell has a smaller porosity than a sub-electrode of the carbon-based electrode with a large geometric surface area located in a higher position in the electrochemical cell closer to the upper part of the electrochemical cell.

16. The electrochemical cell according to any one of claims 12 to 15, characterized in that The electrochemical cell is a cell for electrochemical synthesis, an electrochemical wastewater treatment cell, or a microbial fuel cell.

Citation Information

Patent Citations

  • Large-sized electrode

    EP1229149A1

  • Current density distributor for use in an electrode

    US20160010227A1

  • Carbon article comprising pieces of carbonaceous material bonded with one another and process for producing the same

    US4777083A

  • Current collector for use in a fuel cell

    US20040161659A1

  • Low pressure fuel cell system

    US5709961A